ANALISIS NILAI MORAL PADA CERITA PENDEK MAJALAH BOBO - Cut Elfida Mutia (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2020)
This study aims to describe the moral values contained in Bobo Magazine. The sources of data in this study were 12 short stories in Bobo Magazine from January to December 2019. The data in this study were short stories published in Bobo Magazine in 2019. The method used in this study was a descriptive qualitative method with content analysis. Data collection used the documentation method using reading techniques and note-taking techniques. The results of the study stated that 12 short stories in the analyzed Bobo Magazine had moral values in them. First, moral values related to oneself are (1) brave, (2) self-confidence, (3) hard work, (4) confidence, (5) self-defense, (6) not blaming others, (7) feeling curious, (8) healthy living, (9) self-awareness, (10) independent, (11) patient, (12) enterprising, (13) discipline, (14) diligent, and (15) enthusiasm. Second, moral values relating to others include (1) courtesy, (2) not disturbing others, (3) being helpful, (4) being friends, (5) being kind to others, (6) being friendly, (7) negotiating, (8) caring, (9) returning people's property, (10) not stealing, (11) keeping promises, (12) being kind to parents, (13) advising each other, (14) respect, (15) intimacy , (16) obedient, (17) longing for family, (18) orderly, (19) love to give, (20) cooperation, and (21) not fighting. Third, the moral value of human relations with God, there is only one moral value, namely prayer. Fourth, the human relationship with the natural environment there is only one moral value, namely plant love. The moral values that were delivered directly that appeared in the 2019 Bobo Magazine were 73 short story quotes. Submission through the characters contained in 40 citations while through the description of the authors contained in 33 citations. In the technique of delivering moral values indirectly that appears as many as 3 data quotations, namely through events in the short story.